Engaging vestiges of negative social memory: from an order of segregation to linkage - Wren-Sargent, Tomas (School of Architecture, Planning and Geomatics, 2018)
The theme of this project is the architectural opportunities of spaces of negative social memory. The issue that the work focuses on specifically is the case of the former Non-White Main Line Concourse building, located on the flyover of the Cape Town Train Station precinct. The building has slowly deteriorated since the end of apartheid when its function was made redundant. Today it stands as a squalid remnant of the segregated society it was built to serve. Damaged and decaying, it provides an opportunity for powerful architectural transformation. This project establishes a value in the negative social memory that the building holds, presenting an opportunity to transform the site into a powerful architecture that encourages society to learn from the injustices the building enforced. Through understanding the spatial potentials of the building, a design intention of integration emerges, able to subvert the segregated nature of the existing. The paper locates itself as a research piece on the opportunities presented by remnants of socially and politically challenging histories.